Comment on "Nuclear genomic sequences reveal that polar bears are an old and distinct bear lineage". - Nakagome, Shigeki; Mano, Shuhei; Hasegawa, Masami (My University, 2013)
Based on nuclear and mitochondrial DNA, Hailer et al. (Reports, 20 April 2012, p. 344) suggested early divergence of polar bears from a common ancestor with brown bears and subsequent introgression. Our population genetic analysis that traces each of the genealogies in the independent nuclear loci does not support the evolutionary model proposed by the authors.
PUBLISHED
Keywords: Polar bears; Nuclear genomic sequences; Mitochondrial DNA; Nuclear DNA; Bears